Processo criativo no ensino médio: interdisciplinaridade entre arte/teatro e língua portuguesa - Amarildo Alexandre de Paula Alonso do Carmo (2021)
This dissertation presents, through the analytical description of the creative process of four shows built with students from the Estadual Técnico Industrial Professor Fontes school (in Belo Horizonte/Minas Gerais), the investigation about the possibilities of interdisciplinarity between Art/Theatre and Portuguese Language in High School. Therefore, a literature review on the theme of interdisciplinarity was elaborated and eight former students and two teachers who watched or participated in these creative processes were interviewed. From the survey and analysis of collected data, it was demonstrated that the experience lived in an interdisciplinary way in creative processes, in addition to contributing to the expansion of the knowledge about Portuguese Language and Art/Theater can also develop the ability to elaborate, read and think about the world and encourage the formulation of interdisciplinary pedagogical proposals for teaching Art/Theater in High School.